2023
DOI: 10.1037/men0000408
|View full text |Cite
|
Sign up to set email alerts
|

Status loss due to COVID-19, traditional masculinity, and their association with recent suicide attempts and suicidal ideation.

Abstract: Public Significance StatementStatus loss due to the COVID-19 pandemic, particularly among men with strong endorsement of traditional masculinity ideologies, may play a critical role in understanding the elevated suicide rates in the aftermath of the most acute phase of the COVID-19 pandemic. Health care policy should specifically target men with experienced status loss due to the COVID-19 pandemic in suicide prevention programs and swiftly design mental health care campaigns tailored to the group of men with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 91 publications
0
21
0
Order By: Relevance
“…For example, a study by Coleman et al (2020) found men with strong TMI to be more than twice as likely to die by suicide than men with low TMI, while also being less likely to disclose suicidal ideation. Concordantly, Walther et al (2022) found men with strong TMI who experienced status loss – status being a core dimension in many conceptualizations of TMI – to be about four times more likely to have attempted suicide in the past month. Particularly masculinity norms revolving around stoicism, self-reliance, and verbal aggression have been found to increase suicidal desire among men who experience psychological distress ( Daruwala et al, 2021 ).…”
Section: Introductionmentioning
confidence: 85%
“…For example, a study by Coleman et al (2020) found men with strong TMI to be more than twice as likely to die by suicide than men with low TMI, while also being less likely to disclose suicidal ideation. Concordantly, Walther et al (2022) found men with strong TMI who experienced status loss – status being a core dimension in many conceptualizations of TMI – to be about four times more likely to have attempted suicide in the past month. Particularly masculinity norms revolving around stoicism, self-reliance, and verbal aggression have been found to increase suicidal desire among men who experience psychological distress ( Daruwala et al, 2021 ).…”
Section: Introductionmentioning
confidence: 85%
“…Men are disproportionately likely to commit suicide compared with women, and research is ongoing regarding the psychological and psychiatric antecedents of this observed gender difference (Chandler, 2019, 2022; Green et al, 2018; Green & Jakupcak, 2016; Inckle, 2014). Considering emerging evidence showing a link between masculinity norms, threat, and self-harm (Walther et al, 2022), we propose that this internalized outcome may stem from threat as a function of intrinsic desires to be masculine. Although this hypothesis is difficult to test experimentally, especially in the context of self-harm and suicide, we encourage future researchers to explore this possibility that discrepancies, intrinsic conformity motivations, and masculinity-threatening contexts may combine to result in these extreme forms of internalized responding.…”
Section: Threatmentioning
confidence: 98%
“…Men are disproportionately likely to commit suicide compared to women, and research is ongoing regarding the psychological and psychiatric antecedents of this observed gender difference (Chandler, 2019(Chandler, , 2022Green et al, 2018;Green & Jakupcak, 2016;Inckle, 2014). Considering the emerging evidence showing a link between masculinity norms and internalizing symptoms (e.g., self-harm; Walther et. al, 2022), we propose that these internalized outcomes may stem from threat as a function of intrinsic desires to be more masculine in certain ways.…”
Section: "Breaking": Internalized Responses To Masculinity Threatmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, ChatGPT also briefly mentions positive (or alternative) masculinity, wherein TMI are not only thought of as rigid, maladaptive, and potentially harmful (Eggenberger et al, 2021(Eggenberger et al, , 2022Walther et al, 2022Walther et al, , 2023Wong et al, 2017), but emphasizes the positive aspects of TMI and the masculine gender roles, such as being a family's protector and provider or a good leader (e.g., Englar-Carlson & Kiselica, 2013).…”
Section: Interactionmentioning
confidence: 99%